Identification of Lactic Acid Bacteria From Pandan Civet Feces (P. hermaphroditus) in West Kalimantan Based on Phenotypic Similarity - Ageresya Ester Evelin Br Sibarani; Rahmawati Rahmawati; Firman Saputra (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Lactic acid bacteria are included in the gram positive bacteria that are widely distributed in the digestive tract of living things, such as in the feces of the Pandan Luwak (P. hermaphroditus) and important role in improving the microbial balance in the body. The purpose of this study was to obtain phenotypic characters, types of bacteria and similarity relationship between lactic acid bacteria from feces of Pandan Civet (P. hermaphroditus) in West Kalimantan and lactic acid bacteria in the identification book Bergey's manual of determinative bacteriology. This research was conducted by the method of isolation and screening bacteria using MRSA media supplemented with CaCO3 1%. Characterization of lactic acid bacteria based on morphological, biochemical, and physiological characters in Bergey's Manual of Determination Bacteriology. The results of the analysis using the MVSP (Multivariant Statistic Package) program with SSM coefficients and the UPGMA method obtained 44 bacterial isolates thought to belong to two genera, namely the genus Lactobacillus and Bifidobacterium with three species, namely L. casei, L. brevis and B. bifidum. The results of the analysis showed that 12 bacterial isolates had a similarity index of 87,6% to L. casei, 17 bacterial isolates had a similarity index of 92,2% to B. bifidum and 15 bacterial isolates had a similarity index of 84,5% to L. brevis.